2004
DOI: 10.1038/sj.emboj.7600501
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB/Egr-1/Gadd45 are sequentially activated upon UVB irradiation to mediate epidermal cell death

Abstract: Chronic sun exposure can lead to severe skin disorders such as carcinogenesis. The cell death process triggered by ultraviolet B (UVB) irradiation is crucial because it protects the surrounding tissue from the emergence and the accumulation of cells that bear the risk of becoming transformed. Here, we show that repression of NF-jB and Egr-1 expression drastically inhibits UVB-mediated cell death. Furthermore, we demonstrate that Egr-1 is induced upon UVB irradiation through NF-jB activation and the binding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
130
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(137 citation statements)
references
References 39 publications
(44 reference statements)
5
130
1
1
Order By: Relevance
“…In contrast, a very recent study described activation of NF-kB by UVB via an unknown mechanism, which resulted in activation of the transcription factor Egr-1, followed by Egr-1-dependent activation of Gadd 45a/b, which are involved in the nucleotide excision repair. In contrast to the previous observations in which activation of NF-kB by DNA-damaging agents prevented apoptosis, this UVB-triggered cascade contributed to promotion of UVB-induced cell death in epidermal cells (Thyss et al, 2005). This indicates that the impact of NF-kB activation on apoptosis can be heterogenous and thus appears to be a rather complex process.…”
Section: Discussioncontrasting
confidence: 86%
“…In contrast, a very recent study described activation of NF-kB by UVB via an unknown mechanism, which resulted in activation of the transcription factor Egr-1, followed by Egr-1-dependent activation of Gadd 45a/b, which are involved in the nucleotide excision repair. In contrast to the previous observations in which activation of NF-kB by DNA-damaging agents prevented apoptosis, this UVB-triggered cascade contributed to promotion of UVB-induced cell death in epidermal cells (Thyss et al, 2005). This indicates that the impact of NF-kB activation on apoptosis can be heterogenous and thus appears to be a rather complex process.…”
Section: Discussioncontrasting
confidence: 86%
“…NF-kB and EGR-1 have been shown to cooperatively stimulate chemokine gene transcription (49). Moreover, the EGR-1 promoter includes an NF-kB binding motif that is important for the regulation of EGR-1 expression (50). Results from the current study suggested that ATF3 epigenetically regulated EGR-1 expression by recruiting HDAC1 protein (Fig.…”
Section: Discussionmentioning
confidence: 50%
“…7A) [33,34]. PGE 2 treatment of HCA-7 cells transiently transfected with pEgr-1A construct resulted in significant increase in luciferase activity compared to the vehicle-treated cells (Fig.…”
Section: Creb Phosphorylation By Erk Is Attenuated By L-161982mentioning
confidence: 85%